PERAN GURU AKIDAH AKHLAK DALAM MEMBINA AKHLAK BAGI SISWA MADRASAH ALIYAH NOER FADILAH SUMBER PANJALIN AKKOR PALENGAAN PAMEKASAN - Supandi Supandi; Ahmadi Ahmadi (Journal of Education Partner, 2023)
Progress in the fields of science and technology is increasingly rapid, causing the younger generation to lose their good identity as eastern people who always uphold the values ​​of politeness and also their identity as Muslims. In response to this, Madrasahs as formal Islamic education institutions try to anticipate and deal with their students, including what is done by the moral aqidah teacher at Madrasah Aliyah Noer Fadilah Sumber Panjalin Akkor Palengaan Pamekasan. The focus of this research is: What is the role of the Aqidah Akhlak teacher in fostering good morals for Madrasah Aliyah Noer Fadilah Sumber Panjalin Akkor Palengaan Pamekasan students? and What are the supporting and inhibiting factors faced by the teacher of moral beliefs? The research method used is a qualitative approach with a qualitative descriptive research type. From the research results, it can be understood that the role of Mr. Mohamad Zaini, M.Pd. as a moral aqidah teacher, you don't just carry out your role as a teacher of the material but also in practicing the values ​​expressed and implied in the moral aqidah material taught with a total approach and strategy, not only in the madrasah environment but also outside. In fact, he often visits students' homes to educate their parents. As for supporting factors, one of them is the support of the school principal. Meanwhile, one of the obstacles is: parents' lack of awareness and understanding of the importance of supervising children when they are at home.